Respuesta :
In order to figure this our we need to solve the problem:
5x – 2(3x + 5) = 32
Start by distributing the 2:
[tex]5x+(-2)(3x)+(-2)(5)=32[/tex]
Now we have:
[tex]5x-6x-10=32 [/tex] (Option D is seen here)
Combine like terms:
[tex](5x-6x)+(-10)=32[/tex]
Now we have:
[tex]-x-10=32 [/tex] (Option C is seen here)
Add 10 to both sides:
tex]-x-10+10=32+10 [/tex]
Now we have :
[tex]-x=42[/tex](This is seen in both option A and B)
You've made a mistake in typing your options. All of the options you've given are involved.
5x – 2(3x + 5) = 32
Start by distributing the 2:
[tex]5x+(-2)(3x)+(-2)(5)=32[/tex]
Now we have:
[tex]5x-6x-10=32 [/tex] (Option D is seen here)
Combine like terms:
[tex](5x-6x)+(-10)=32[/tex]
Now we have:
[tex]-x-10=32 [/tex] (Option C is seen here)
Add 10 to both sides:
tex]-x-10+10=32+10 [/tex]
Now we have :
[tex]-x=42[/tex](This is seen in both option A and B)
You've made a mistake in typing your options. All of the options you've given are involved.